Hedges and Safe Havens An Examination of Stocks, Bonds, Oil, Gold and the Dollar - GURDGIEV, CONSTANTIN; LUCEY, BRIAN MICHAEL (My University, 2011)
We investigate five major financial asset classes, examining how and under what circumstances each may act as a hedge or a safe haven to each other. Using the approach of Baur and Lucey (2010) and Baur and McDermott (2010) we find that , in line with conventional investment strategies, gold acts as a safe haven for most assets, except oil. Bonds do not appear to be a longterm hedge against equity price movements but do act as a safe haven for equities.
PUBLISHED
Keywords: Economics; Business; DCC Garch; Gold